'Beyond the Dance Floor'? Gendered Publics and Creative Practices in Electronic Dance Music. Issue 1 (2nd January 2016) - Stirling, Christabel
Abstract : This article draws on ethnographic fieldwork in London (2013–2014) to address the reasons why men dominate the crowds in certain spheres of electronic/dance music. Focusing on a group of London-based genres, notably dub, dubstep, grime and 'bass music', I analyse how gender gets attached to musical formations through the qualities and connotations not only of musical sound, but of its material, technological, social and spatial mediations. I show how such connotations 'stick' (Ahmed, S. [2004 ]. The cultural politics of emotion. Edinburgh: Edinburgh University Press) and get transmitted through time, leading to the persistent absence of women from certain musical lineages; and I demonstrate how this process serves to entrench and 'naturalise' associations between musical genres and 'maleness'. I then take this analysis to creative practices. Through my dialogue with DJ/producer Jack Latham—aka Jam City (Night Slugs)—I illuminate how musicians caught up in gendered socio-musical formations can become reflexively engaged with the gendered implications of the sounds they produce, and can therefore experiment with making changes.